2017
DOI: 10.3126/hren.v13i2.17548
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of depot medroxyprogesterone in women attending general outpatient department: A cross sectional study

Abstract: Background: Depomedroxy progesterone (DMPA) is most commonly used contraception

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The most sought after reason by users was easy to follow dose (30%) whereas difficulty with compliance (26%) with other methods remains the next important reason. 9 The most common reason for non-acceptability in this study was "fear of side effects" (44.2%) followed by Unwillingness from husband or family from any injection (18.8%).…”
Section: Dmpamentioning
confidence: 68%
“…The most sought after reason by users was easy to follow dose (30%) whereas difficulty with compliance (26%) with other methods remains the next important reason. 9 The most common reason for non-acceptability in this study was "fear of side effects" (44.2%) followed by Unwillingness from husband or family from any injection (18.8%).…”
Section: Dmpamentioning
confidence: 68%
“…This could be because DMPA offers privacy and is easy and convenient to use. [31] A study in Nigeria found that DMPA was the most-preferred method because women did not want to reveal to their partners that they were using contraceptives. [32] DMPA also might be preferred because the privacy it allows may help minimize disagreements between partners.…”
Section: Discussionmentioning
confidence: 99%